Good or Bad? The Ambivalent Leader-Follower Relationships - Zhao, Qinglin; Zhou, Wenxia (Frontiers in Psychology, 2021)
Researchers have emphasized the positive and negative influences of ambivalent leader-follower relationships, but it is not clear when the ambivalent relationship is associated with good or bad influences. To answer this question, we reviewed the definition and identified ten different types of ambivalent leader-follower relationships. Further, we demonstrate the negative outcomes (more inflexibility, disengagement, and worse performance) can be explained by the workplace stressor perspective, and the positive outcomes (more flexibility, engagement, and better performance) can be explained by paradox view. Finally, drawing from conservation of resources theory (COR), we integrate workplace stressor framework and the paradox view to address that when the ambivalent leader-follower relationship is beneficial or detrimental for followers. We proposed that the degree of ambivalence, support from the third party, and follower’s integrative complexity will influence the possible positive or negative influences. Limitations and future directions were also discussed.